Determinação da usinabilidade dos aços ferramentas N2711M e VPATLAS no fresamento de topo - Montalvão, Jairo de Almeida (2014)
The expansion of mold and die sector in the last decades together with new technologies and manufacturer competitiveness demand the development of new materials by the metallurgical industries to supply the market with lower cost. When manufacturing mold and dies the highest cost is related to the machining process, therefore each developed material demands a complete study of its machinability, determining its manufacturing characteristics, envisaging a better performance of the process with economy. The objective of the present work is to determine the machinability of two tool steels used for manufacturing of mold and dies, the N2711M, classified as a martensitic steel, and VPATLAS, classified as a banitic steel. The machining characteristics of these two steels were determined by tool life tests, using an optimization program to determine the coefficients of the Expanded Taylor s equation, machining forces, torque, power consumption, surface roughness and analysis of the swarfs when end milling them with coated cemented carbide tools. The results allowed comparisons of the machinability of the materials and it was possible to conclude that in terms of tool life the N2711 steel presented better performance. However, for both materials, lower tool lives were achieved for higher feed rates. As to the surface roughness and machining forces, the results did not show significant differences. These are important results for the mold and die industry that normally uses these steels and also for the tool stell makers.